Tracking cell turnover in human brain using 15N-thymidine imaging mass spectrometry - Roeder, Sebastian S.; Bonnin, Elisa A.; Wu, Ting-Di; Guerquin-Kern, Jean-Luc; Jabari, Samir; Brandner, Sebastian; Eyüpoglu, Ilker Y.; Gollwitzer, Stephanie; Hamer, Hajo M.; Gerner, Stefan T.; Doeppner, Thorsten R.; Rummel, Christoph; et al. (Frontiers in Neuroscience, 2023)
Because of requested revisions within the abstract, the abstract has overlength and cannot be copied here. PLease see the revised Abstract within the revision files.